PERLINDUNGAN HUKUM TERHADAP KREDITUR ATAS JAMINAN HAK GUNA BANGUNAN YANG TELAH BERAKHIR MASA BERLAKU DAN MASIH DIBEBANI HAK TANGGUNGAN - Ramadhan, Muhammad Akbar; Yudha Cahya Kumala; Marni Emmy Mustafa (Journal of Innovation Research and Knowledge, 2025)
Building Use Rights are one of the land rights regulated in the UUPA which can be used as an object of collateral for Mortgage Rights as regulated in the UUHT. The phenomenon that occurs when objects of Mortgage Rights are guaranteed with the status of Building Use Rights whose validity period has expired results in the abolition of the Mortgage Rights as stated in Article 18 paragraph (1) letter d UUHT. This research aims to formulate the problem, namely: What is the legal protection for creditors against building use rights collateral objects that have expired and are still encumbered with mortgage rights? And what are the legal consequences for land collateral objects with Building Use Rights that have expired and are still encumbered with Mortgage Rights? The theory used in this research is the Legal Protection Theory according to Satjipto Rahardjo, the Legal Consequences Theory according to Soeroso. The method used in this research is normative juridical (library law research or secondary data with primary, secondary and tertiary sources of legal materials). The research approaches used are statutory, conceptual, case and analytical approaches with legal material collection techniques carried out by identifying and inventorying legal rules, book literature and other legal materials. Legal material analysis techniques are carried out using grammatical legal interpretation and systematic interpretation. From the results of the research, it was concluded that legal protection for creditors with HGB status collateral objects which have expired before the credit matures is by providing a credit period that is shorter than the validity period of the rights status, extending rights at the initial time of the credit agreement or extending credit by making a power of attorney. to the bank, change the rights from HGB to Ownership Rights, and ask for replacement collateral or additional collateral. As well as recharging Mortgage Rights on land objects of collateral which have expired and have been renewed within the credit period. The legal consequences of ending the rights status of HGB collateral objects which are still encumbered with Liability Rights will result in the abolition of the Mortgage Rights (Article 18 paragraph (1) letter d UUHT). Thus changing the position of creditors holding Mortgage Rights from preferred creditors to concurrent creditors who have individual rights which are rights arising from general guarantees regulated by Article 1131 of the Civil Code.